2013
DOI: 10.1371/journal.pone.0075005
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase 1 Serves as a Pro-Viral Factor by Regulating Viral RNA Synthesis and Nuclear Export of Viral Ribonucleoprotein Complex upon Influenza Virus Infection

Abstract: Influenza continues to pose a threat to humans by causing significant morbidity and mortality. Thus, it is imperative to investigate mechanisms by which influenza virus manipulates the function of host factors and cellular signal pathways. In this study, we demonstrate that influenza virus increases the expression and activation of sphingosine kinase (SK) 1, which in turn regulates diverse cellular signaling pathways. Inhibition of SK suppressed virus-induced NF-κB activation and markedly reduced the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(116 citation statements)
references
References 65 publications
2
114
0
Order By: Relevance
“…The virus was amplified on Madin-Darby canine kidney (MDCK) epithelial cells as described elsewhere (33)(34)(35). Virus infection and titration studies were performed as described previously (33,(36)(37)(38). For the infection, cells were incubated with IAV for 1 h and then incubated with the medium.…”
Section: Virus and Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The virus was amplified on Madin-Darby canine kidney (MDCK) epithelial cells as described elsewhere (33)(34)(35). Virus infection and titration studies were performed as described previously (33,(36)(37)(38). For the infection, cells were incubated with IAV for 1 h and then incubated with the medium.…”
Section: Virus and Cellsmentioning
confidence: 99%
“…For the plaque assay, using serial dilutions of culture supernatants, viruses were adsorbed onto 2 ϫ 10 5 MDCK cells/ml for 1 h, and then the cells were incubated with 2ϫ Eagle's minimum essential medium (EMEM; Gibco) mixed with an equal portion of 1% agarose (SeaKem ME). Human embryonic kidney (HEK) 293 cells, human lung epithelial A549 cells, and African green monkey kidney Vero cells were cultured in Dulbecco's modified Eagle's medium (DMEM; Gibco) as explained elsewhere (35,36,39). MDCK cells were cultured in minimum essential medium Eagle (MEM; Mediatech).…”
Section: Virus and Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown close association between SPK/S1P pathway and important cellular processes such as cell growth, inflammation and immune responses, with both types of SPKs having the opposing effects (Maceyka et al, 2005; Okada et al, 2005; Olivera et al, 1999; Snider, Alexa Orr Gandy & Obeid, 2010). Interestingly, in addition to its contribution towards the development of degenerative diseases in humans, SPKs also play important roles in several viral infections, including Dengue and Influenza A viruses for SPK1 as well as Hepatitis C virus, Kaposi’s sarcoma-associated herpes virus, and most importantly for our study, CHIKV for SPK2 (Clarke et al, 2016; Couttas et al, 2014; Dai et al, 2014; Reid et al, 2015; Seo et al, 2013; Yamane et al, 2014). …”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, 41 of the 199 druggable cellular factors were shown to be implicated in IAV infection (Table S2) [10,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,...…”
Section: Combination Of Various Omics Techniques Identifies Potentmentioning
confidence: 99%